Impact of PM2.5 Concentration on Winter Light Rain in North China - Xiong Na; Zang Zengliang; Liu Lang (E3S Web of Conferences)
This study investigated the spatial distribution and temporal variations of winter PM2.5 concentrations and light precipitation in North China from 2013 to 2022, and explored the relationship between them. The results show that winter PM2.5 concentrations in North China exhibit a south-high-north-low spatial pattern, with higher concentrations in the east than in the west, and a maximum average PM2.5 concentration exceeding 100 μg/m3. The overall interannual PM2.5 concentration shows a decreasing trend, which is most significant in the northern part of Hebei Province. Winter precipitation in North China demonstrates a similar south-high-north-low spatial pattern, with an upward trend in mean annual precipitation. PM2.5 concentration changes predominantly influence the frequency of light rainfall events. The relationship between PM2.5 concentrations and light rainfall frequency shows a clear spatial pattern: a significant positive correlation is observed west of the Taihang-Yanshan mountain range, and a negative correlation east of the mountain range. This occurs because rainfall frequency initially increases then decreases with increasing PM2.5 concentration. The differing background PM2.5 concentrations on either side of the mountain range result in opposing trends in light rainfall frequency relative to PM2.5 concentration changes.